Execution of Diaphragm and Cut-Off-Walls in Rock – Applications, Performance and Limits - Franz-Werner Gerressen; Albert Neumann; Giancarlo Santarelli (Deep Foundations Institute, 2016)
"Diaphragm walls are known as underground structural elements commonly used for retention systems and permanent foundation walls or elements. In addition they are also quite often used as deep groundwater barriers, named Cut-Off-Walls (COW). Due to the requirements of each particular job site, e.g. the need for carrying high loads or as seepage barriers, there is an increasing industry demand for efficiently cutting into rock. Besides the removal of boulders, cutting through rock, is always the most difficult part of the excavation process of a diaphragm wall or COW.There are a number of influencing factors which have an impact on the rock cutting performance. Besides the influence of the rock characteristics itself, which is not always the same, there are other factors related to equipment, tooling as well as the operating staff. In addition to RQD, the most commonly available rock property found in geotechnical reports is the Unconfined Compressive Strength (UCS) value. There are however some other related properties, such as weathering, bedding, inclination, abrasiveness, etc.,which can have a major impact on the achievable cutting performance. This paper will discuss the various parameters, and how they can be considered for performance estimation. Based on experiences gained on over 100 projects, a performance estimation chart was developed to allow for a better approach to these kinds of projects. This paper also explains the general installation process in as well as some specific features related to specific site conditions. In addition, some job site references will give more detailed information about such type of site conditions and how to deal with them.Keywords: Diaphragm wall, Cut-Off-Wall, Trench Cutter, RockINTRODUCTIONDiaphragm walls are known as underground structural elements commonly used as retention systems for excavation pits, shafts, permanent foundation walls and load bearing elements.It can be anticipated that, with the increasing trend of utilizing more and more underground space to accommodate environmental considerations and urban/suburban development, there will be an increasing requirement for diaphragm wall usage in even more difficult conditions.In addition diaphragm walls can also be used as deep groundwater barriers (Cut-Off-Walls). This market has demonstrated that the demand for these types of walls is reaching ever more difficult soil conditions and greater depths which are surpassing the current industry standards. The trench cutter is the most important tool for performing this type of work."